2018
DOI: 10.5194/bg-15-2649-2018
|View full text |Cite
|
Sign up to set email alerts
|

The competing impacts of climate change and nutrient reductions on dissolved oxygen in Chesapeake Bay

Abstract: Abstract. The Chesapeake Bay region is projected to experience changes in temperature, sea level, and precipitation as a result of climate change. This research uses an estuarine-watershed hydrodynamic-biogeochemical modeling system along with projected mid-21st-century changes in temperature, freshwater flow, and sea level rise to explore the impact climate change may have on future Chesapeake Bay dissolved-oxygen (DO) concentrations and the potential success of nutrient reductions in attaining mandated estua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(157 citation statements)
references
References 55 publications
9
146
1
1
Order By: Relevance
“…Specifically we predict to see the largest increase in cumulative hypoxic volume between oxygen concentrations of 2 and 5 mg l −1 [12], which is too hypoxic for many marine species to inhabit [13]. This flux of hypoxic water that typically occurs midsummer is expected to occur earlier in the year as well [12].…”
Section: Introductionmentioning
confidence: 90%
“…Specifically we predict to see the largest increase in cumulative hypoxic volume between oxygen concentrations of 2 and 5 mg l −1 [12], which is too hypoxic for many marine species to inhabit [13]. This flux of hypoxic water that typically occurs midsummer is expected to occur earlier in the year as well [12].…”
Section: Introductionmentioning
confidence: 90%
“…For warming scenarios, we consider temperature increases consistent with previous studies of climate change in the Gulf (Justi c et al 1996. For scenarios combining nutrient decreases and higher water temperatures, we select +2°C, congruous with other studies of hypoxia under climate change projections (Justi c et al 1996, Del Giudice et al 2018b, Irby et al 2018. Scenarios consider the effect of temperature on both oxygen saturation (O s ) and benthic respiration (D s ) through the mechanisms described above.…”
Section: Scenario Projectionsmentioning
confidence: 99%
“…This leads to the question of whether or not these results would stand if climate change impacts were added to the analysis. Although this study demonstrated that the current regulatory nutrient reductions are likely to eventually produce the required DO improvements under the present climate, it is not clear that the established nutrient loads will be adequate under near-term future climate conditions that include rising temperature and sea level along with changes in precipitation patterns (Irby et al 2018).…”
Section: Discussionmentioning
confidence: 77%